Search for the dark photon in B 0 → A′A′, A′ → e + e − , μ + μ − , and π + π − decays at Belle - The BELLE collaboration; S.-H. Park; Y.-J. Kwon; I. Adachi; H. Aihara; S. Al Said; D. M. Asner; H. Atmacan; T. Aushev; R. Ayad; V. Babu; P. Behera; et al. (Journal of High Energy Physics, 2021)
Abstract We present a search for the dark photon A′ in the B 0 → A′A′ decays, where A′ subsequently decays to e + e − , μ + μ − , and π + π − . The search is performed by analyzing 772 × 106 B B ¯ $$ B\overline{B} $$ events collected by the Belle detector at the KEKB e + e − energy-asymmetric collider at the ϒ(4S) resonance. No signal is found in the dark photon mass range 0.01 GeV/c 2 ≤ m A′ ≤ 2.62 GeV/c 2, and we set upper limits of the branching fraction of B 0 → A′A′ at the 90% confidence level. The products of branching fractions, ℬ B 0 → A ′ A ′ × ℬ A ′ → e + e − 2 $$ \mathrm{\mathcal{B}}\left(B^0→ A^{′ }A^{′}\right)× \mathrm{\mathcal{B}}{\left(A′ → {e}^{+}{e}^{-}\right)}^2 $$ and ℬ B 0 → A ′ A ′ × ℬ A ′ → μ + μ − 2 $$ \mathrm{\mathcal{B}}\left(B^0→ A^{′ }A^{′}\right)× \mathrm{\mathcal{B}}{\left(A′ → μ^{+}{μ}^{-}\right)}^2 $$ , have limits of the order of 10 −8 depending on the A′ mass. Furthermore, considering A′ decay rate to each pair of charged particles, the upper limits of ℬ B 0 → A ′ A ′ $$ \mathrm{\mathcal{B}}\left(B^0→ A^{′ }A^{′}\right) $$ are of the order of 10 −8–10 −5. From the upper limits of ℬ B 0 → A ′ A ′ $$ \mathrm{\mathcal{B}}\left(B^0→ A^{′ }A^{′}\right) $$ , we obtain the Higgs portal coupling for each assumed dark photon and dark Higgs mass. The Higgs portal couplings are of the order of 10 −2–10 −1 at m h ′ ≃ m B 0 $$ {m}_{h′}\simeq {m}_{B^0} $$ ± 40 MeV/c 2 and 10 −1–1 at m h ′ ≃ m B 0 $$ {m}_{h′}\simeq {m}_{B^0} $$ ± 3 GeV/c 2.